The effects of leadership behaviour on employee work engagement in Academia in the South African context - Shangase, Thobani Paul (My University, 2018)
The purpose of this research was to investigate the relationship between leadership behaviours namely task-oriented and person-oriented; and their influence on employee work engagement in academia in the South African context. Task-oriented behaviours were defined by Brown, (2003) as those that involve being proactive at task related activities such as planning and implementation. Ellemers, De Gilder and Van Den Heuvel, (1998) explained that these behaviours allow the employee to desire increased work performance for the purposes of personal advancement. Schaufeli & Bakker, (2010) described this work engagement process as that where employees deliver organisational goals by delivering high quality results. The main research questions in this study investigate the direct effects of person-oriented and task-oriented behaviours on work engagement. The methodology adopted to measure these leadership behaviours was a survey that used elements of the 360-feedback tool, Multifactor Leadership Questionnaire (MLQ) and Utrecht Work Engagement Scale (UWES). The procedure was like that of Xu, (2011) JRA 360 feedback tool, although the participants in this study were in an academic organisation and a different country. Participants in the research consisted of 34 employees and 10 leaders who work at the University of Witwatersrand across 4 different faculties namely engineering, commerce, health sciences and humanities. The employees were of varying positions within the departments and had different academic and biographical details. This study used statistical analyses including regression and correlation analysis in order to understand the influence of the multiple constructs of leadership behaviour and those of employee engagement. In previous studies by Brown, (2003) it was found that correlations for the leadership behaviours that are person-oriented (e.g. motivational) showed multi-collinearity among all the person-oriented subconstructs. While in studies Ozyapar, (2017) it was reported that task-oriented behaviours allow leaders to possess the ability to affect the 2 drivers of the employee’s work engagement. Reliability studies for this research used internal consistency to investigate patterns in order to make meaningful conclusions. Validation was through the control of sample size and time frames (Yu, 2005). This study found that stimulating social support was the most favoured person-oriented leadership behaviour. While the one that was favoured amongst task-oriented behaviours was structure initiation. These two behaviours resulted in an increased amount of work engagement. It was further found that there exists a direct relationship between social support with an increased amount of vigor. Additionally, there was also a direct relationship between, initiating structure and an increased amount of dedication and work absorption. The effects of these behaviours on these work engagement constructs caused an increased amount of work engagement and consequently organisational performance. It was further emphasised in the recommendations that for future research it would be advisable that a tool for relating leadership behaviour and work engagement be developed. This study is relevant today as it adds to literature and provides a full framework of comparing leadership behaviour across countries. The reader will have a perspective of the influences of leadership behaviour on work engagement in the South African space. This study will assist managers and academic leaders by changing their organisations towards creating an environment that allow engaged employees. Engaged employees are more productive, customer centric, and generate financial success.
MBA
Keywords: Leadership. Management.